Nutritional and anti-nutritional evaluation of injera made from Sorghum, Rice, Teff, and Flaxseed flours using D-optimal mixture design - Moges Amtataw; Estifanos Kassahun; Solomon Tibebu; Tadele Andargie; Takele Ayanaw; Agimassie Agazie; Mesfin Wogayehu; Abebaw Teshome; Sadik Jemal; Deginet Teferi (Scientific Reports)
Abstract Injera, a fermented staple food traditionally made from Teff flour, is a key part of the Ethiopian diet, with nearly all Ethiopians eating it at least once daily. Compositing various grain-based, and oilseed flours with Teff flour improves the nutritional content, and cost-effectiveness of the produced Injera. In Ethiopia, very limited studies were conducted to investigate the use of sorghum, rice, and teff flour blends combined with flaxseed flour in Injera preparation. Thus, this study was conducted to evaluate the anti-nutritional factors, microbiological characteristics, and ideal blending proportions of sorghum, rice, teff, and flaxseed flours to create a superior quality Injera via D-optimal design. One-way and two-way ANOVA, alongside Tukey’s pairwise comparison method, was employed to assess mean differences. The aim was to enhance the nutritional quality of Injera compared to a control sample made from 100% sorghum flour. The optimal nutritional profile was achieved with a blend comprising 50% sorghum, 20% rice, 30% teff, and supplemented with 3% flaxseed flour. This blend resulted in Injera containing 3.02% fiber, 9.30% protein, 83.16% carbohydrate, 393.24 kcal/100 g energy, 13.99 mg/100 g iron, 4.06 mg/100 g calcium, and 3.78 mg/100 g zinc. The optimization process identified this blend as optimal for improving the nutritional quality of Injera. The findings underscore that blending teff with sorghum, rice, and flaxseed flour enhances the nutritive value of Injera.